PERAN KELUARGA TERHADAP KEPATUHAN MINUM OBAT PADA PASIEN TB PARU: LITERATUR REVIEW - Dyah Ika Krisnawati; Muhamad Khafid; Nety Mawarda Hatmanti; Priyo Mukti Pribadi Winoto; Lilik Faizzatullailiyah; Izma Fatiqul Qasanah (Jurnal Kesehatan Islam : Islamic Health Journal, 2024)
Abstract Introduction: Pulmonary Tuberculosis (TB) is one of the global public health challenges that has long been known and is still a health problem in various countries in the world. Non-compliance with taking medication arises due to several factors including lack of motivation among families to carry out the role of the family in providing assistance in compliance with taking medication for family members suffering from pulmonary TB. The impact of the lack of family role on compliance with taking medication in members of patients suffering from pulmonary TB is that the death rate continues to increase and the emergence of drug resistance, as well as the occurrence of relapses so that they must undergo second-line treatment. The purpose of this literature review is to analyze publications related to the role of the family in compliance with taking medication for patients with pulmonary TB. Method: The design of this study is a literature review using the inclusion exclusion method with the PECOS format. The search method in this study uses the Google Scholar and Pubmed databases in an empirical study in the last 10 years as many as 6 journals that are in accordance with the study. Analysis results: show that family support plays a very important role in maintaining patient compliance in taking their medication. Conclusion: Based on the reviewed journals, the six journals show that there is a role for the family in compliance with taking medication in pulmonary TB patients, therefore success in treating pulmonary TB requires support from both motivation, supervision, and family education to patients with routine treatment of taking OAT. Keywords: Family Support, Compliance, Taking Medication, Pulmonary TB